Differences between running activity in tennis training and match-play - Galé-Ansodi, C.; Castellano, J.; Usabiaga, O. (International Journal of Performance Analysis in Sport, 2018)
The aim of this study was to compare the running activity between training and match-play for young high-level tennis players. Ten female and ten male young high-level tennis players took part in the study (13.80 age ±2.08 years). Twelve Portable GPS devices operating at10 Hz were used to collect velocity data. Match-play analysis was carried out by Aragon Tennis Master on hard court and training analysis was carried out by High Level Performance Centre of the Aragon Tennis Federation. The distance covered per minute (DCmin) by players in match-play was higher than in training (Match-play = 50.4 ± 6.0 m· min-1 vs. Training = 34.5 ± 6.2 m· min-1; F(1, 76) = 163.9; p < 0.001; ?2p = 0.64, moderate effect). The acceleration distance covered per minute (DCAmin), was higher in match-play than in training (Match-play = 45.0 ± 3.0 m· min-1 vs. Training = 28.6 ± 6.2 m· min-1; F(1, 76) = 267.6; p < 0.001; ?2p = 0.7, moderate effect). The results showed that match-play was characterised by demanding to players a great number of accelerating efforts, whereas in training, players do not replicate these actions, predominating movements at high average speed than in match-play.